Influence of different fertilization systems on nutritional composition of corn Zea mays L. (Poaceae) and the effects to attack of Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) to storage product - Marsaro Júnior, Alberto Luiz; Lazzari, Sonia Maria Noemberg; Souza, Jacimar Luís de; Lazzari, Flavio Antonio; Cândido, Lys Mary Bileski (Semina: Ciências Agrárias, 2007)
The objective of this research was to evaluate the influence of nutritional composition of grains of different corn cultivars produced under different fertilization systems on resistance of dry kernel against the maize weevil Sitophilus zeamais. Five cultivars of corn were planted (EMCAPA 201, EMCAPA 202, Composto 1, Composto 2, and AG 405), under four fertilization systems: organic, mineral, organic and mineral combined, and in absence of fertilizer.The contents of minerals leaves were evaluated during the period of the feminine florescence. After harvesting, grain production, moisture content, ashes, lipids, proteins and carbohydrates were evaluated. The resistance level of the cultivars was evaluated based on biological parameters of the insect (biological cycle, number of emerged insects and adult weight), susceptibility index, and on grain weight loss caused by insect feeding. In absence of fertilization all the cultivars, in general, present a minor contents of leave minerals. The highest grain production was obtained from the plot with combined fertilization, and the lowest in the unfertilized plot. The content of ashes, lipids and proteins were lower in the kernels from the area without fertilizer, while the carbohydrate levels were higher in this system. The ash content, that reflects minerals levels in the grain, was higher in the organic and combined fertilization areas. The protein levels were higher under combined fertilization. The results did not indicate the existence of a significant effect of the nutritional composition of the grains of different cultivars on development, reproduction and susceptibility index, probably due to the narrow genetic bases of the cultivars tested here.